Menjemput Arsip Hingga ke Belanda: Dari Praktik Manajemen Arsip hingga Akereditasi Kearsipan PT Semen Padang - Putra, Purwanto (UIN Imam Bonjol Padang, 2022)
This study was conducted with the aim of highlighting the importance of archive management and practices at PT Semen Padang. That the extent to which information, records and archives are the